Genetic evolution and codon usage mode of SFTSV - Zhang, Yuhan; Hu, Li; Li, Chao; Wei, Xuemin; Shen, Yuanyuan; Li, Hongfeng; Sai, Lintao; Song, Li; Xu, Yifei (Frontiers in Microbiology, 2026)
IntroductionSevere fever with thrombocytopenia syndrome virus (SFTSV), first identified in Henan Province, China (2009), has since been detected in 26 Chinese provinces and remains a significant public health threat. Despite its spread, key aspects of its molecular evolution, particularly the genetic characterization and codon usage bias, remain understudied.MethodsIn this study, we analyzed blood samples collected in 2022 from six suspected SFTS cases in Jinan, Shandong Province. This was complemented by a comprehensive analysis of whole-genome sequences obtained from the ViPR and GenBank databases, updated through July 2023. Phylogenetic analysis was employed for genotype classification. Potential recombination events were identified using RDP4. Codon usage patterns were investigated through multiple analyses, including ENC-plot, parity rule 2 (PR2) analysis, and neutral evolution analysis.ResultsPhylogenetic analysis revealed that the detected viral strains belonged to genotypes C3 and C1. Recombination analysis identified 99 potential recombination events among 89 viral strains. Codon usage analyses demonstrated a weak codon usage bias in SFTSV. Further evaluation indicated that both natural selection and mutational pressure shape its codon usage patterns, with natural selection being the predominant force in four SFTSV genes.DiscussionOur findings highlight the expanding evolutionary diversity of SFTSV, evidenced by recombination events and distinct genotypes. The elucidation of its codon usage characteristics, primarily driven by natural selection, provides critical insights for advancing SFTSV surveillance, improving disease control strategies, and informing targeted vaccine development.